2020
DOI: 10.17706/ijbbb.2020.10.1.42-48
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Antioxidant Activities, Total Phenolic and Flavonoid Contents of Bee Pollen Crude Extracts

Abstract: Bee pollen is a natural product from honeybees which is rich in bioactive compounds. Bee pollen grain and powder were extracted using conventional and sonication extraction methods. All bee pollen crude extracts could not inhibit growth of test pathogenic bacteria. The antioxidant activity was analyzed via DPPH free radical scavenging activity assay and found that the ethanolic extract of bee pollen grain obtained by conventional method had the highest antioxidant activities (p<0.05), 40.69±3.01 mg GAE/g extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…The use of natural products such as beehive products including honey, pollen, royal jelly, and propolis as a source of antioxidant molecules has been supported and suggested to protect human cells from the effects of oxidative stress by numerous scientific studies [ 142 ]. Moreover, the antioxidant activities of bee pollen have been evaluated in several works using well-known techniques such as DPPH, ABTS, β- carotene, FRAP, CUPRAC, NO, and TAC assays [ 132 , 138 , 140 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 ]. Table 3 summarizes all studies that have evaluated the antioxidant activity of bee pollen.…”
Section: Chemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of natural products such as beehive products including honey, pollen, royal jelly, and propolis as a source of antioxidant molecules has been supported and suggested to protect human cells from the effects of oxidative stress by numerous scientific studies [ 142 ]. Moreover, the antioxidant activities of bee pollen have been evaluated in several works using well-known techniques such as DPPH, ABTS, β- carotene, FRAP, CUPRAC, NO, and TAC assays [ 132 , 138 , 140 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 ]. Table 3 summarizes all studies that have evaluated the antioxidant activity of bee pollen.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Other research works reported a variable antioxidant effect of different bee pollen extracts including those from Algeria, Greece, Italy, Korea, Spain, Slovakia, Malaysia, Serbia, Thailand, and Poland, and this variability can be significantly related to a variety of botanical and geographical origins [ 132 , 140 , 143 , 147 , 148 , 153 , 154 , 156 , 158 , 159 , 163 , 164 , 165 , 170 ].…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Futui and Thongwai 2020 [45] Thailand multifloral Stored at −20 It can be assumed that the adopted extraction process for a bee pollen sample, including the sample pre-treatment, extraction method and solvent, impacts the extraction efficiency of antioxidant constituents and consequently on the level of antioxidant activity measured. The objective of this study was to use the Design of Experiment approach to optimise an extraction process for bee pollen with a view to maximising the extraction of antioxidant constituents as measured by the DPPH, FRAP and TPC assays.…”
Section: Antioxidant Assaysmentioning
confidence: 99%
“…For example, a study by Fatrcová-Šramková et al assessed the antibacterial activity of monofloral bee pollen against pathogenic bacteria and found that Staphylococcus aureus was the most sensitive bacteria to an ethanol extract of poppy pollen, while Salmonella enterica was the most sensitive bacteria to a methanol extract of rape bee pollen and an ethanol extract of sunflower pollen [1]. Similarly, the antibacterial properties of pollen extracts from different plant species found that bee-pollen extracts obtained from plants in the family Papaveraceae, Brassicaceae, and Asteraceae could inhibit the growth of Bacillus subtilis, Escherichia coli, Klebsiella spp., Listeria monocytogenes, Pseudomonas aeruginosa, and Staphylococcus aureus [84]. The antimicrobial activity of pollen can be attributed to the presence of bioactive compounds such as flavonoids, phenolic compounds, and other phytochemicals [85].…”
Section: Bacteriamentioning
confidence: 99%
“…The antifungal properties of bee pollen have been investigated against a wide range of pathogenic fungi, including several species of Candida (C. albicans, C. glabrata and C. krusei) [84,92], Aspergillus species [93], and other pathogenic fungi [89]. However, limited research has focused on elucidating the mechanisms by which it exerts its inhibitory effects on pathogenic fungi.…”
Section: Fungimentioning
confidence: 99%